Evaluation of a rapid diagnostic test for Schistosoma mansoni infection based on the detection of circulating cathodic antigen in urine in Central Sudan. - Mohamed M Elbasheir; Ibrahim A Karti; Elwaleed M Elamin (Public Library of Science (PLoS), 2020)
Background The Kato-Katz thick smear is the standard test for the diagnosis of Schistosoma mansoni infection, but the sensitivity of this technique is low. As an alternative, (CCA) strip test has been evaluated with the conclusion that it may replace the Kato-Katz method in areas where prevalences are moderate or high. Therefore, this study was undertaken to evaluate the performance of the CCA strip test in the diagnosis and monitoring of S. mansoni infection in Sudan. Methodology 489 stool and urine samples were collected from school children in endemic area of Sudan to determine the validity of CCA strip test based on duplicate Kato-Katz thick smear technique. Additional, 118 samples from known non schistosome-endemic area were collected to assess the CCA cross reactivity with other pathogens rather than schistosomiasis. The stability of CCA in urine samples was determined by consecutive examination of 40 positive CCA urine samples. 81 samples were used to evaluate the CCA strip test for the assessment of cure one week, three weeks and six weeks post Praziquantel treatment. Principal findings Assuming parasitological test results as the gold standard, the sensitivity, specificity, positive predictive and negative predictive values of the CCA test were 96%, 85.4%, 78.5% and 97.5% respectively. There was no cross reactivity with other pathogens. The CCA strip test showed high accuracy in monitoring of treatment 93.8% and 100% after three and six weeks of administration of Praziquantel respectively. The stability of the CCA for long time in the urine revealed a safety transportation and shipment of the samples whenever it demanded. Conclusion/significance The uses of urine CCA strip test in the field would provide more accurate information on the epidemiology and monitoring of the Schistosoma mansoni infection in endemic areas of schistosomiasis than the conventional parasitological method. Moreover, The stability of CCA in urine samples confirms a safety transportation period of the samples whenever it required.